Early Childhood Education Curriculum in Japan: A Systematic Literature Review and Insights for Indonesia - Mashadi, Aisya (Jurnal Pendidikan Raudhatul Athfal, 2024)
This study aims to examine the curriculum system in Japan by focusing on five main aspects: (1) the history of the curriculum; (2) curriculum policy; (3) curriculum principles; (4) early childhood education (ECE) curriculum; (5) types of early childhood education institutions in Japan; and (6) insights for Indonesian Early Childhood Education. This research employs a qualitative approach using a literature review method. The subjects of the study include relevant documents such as books, academic articles, and Japanese educational policy documents. Data were collected through literature analysis and analyzed using content analysis techniques, involving repeated reading and cross-referencing of sources to ensure data validity. The results indicate that Japan consistently updates its curriculum every ten years to align with changing times. The curriculum is dynamic, flexible, and modern. The historical development of Japan's curriculum is divided into two major eras: Tokugawa and Meiji. The principle of Chi-Toku-Tai, emphasized in the Japanese curriculum, aligns with Bloom’s taxonomy domains: cognitive, affective, and psychomotor. At the early childhood level, the curriculum for children aged 0–3 focuses on intellectual, social-emotional, and physical development, while for those aged 4–6, it emphasizes structured play, language, arts, and social interaction. Thus, Japan’s early childhood education curriculum reflects a comprehensive and sustainable system, characterized by periodic curriculum revisions, the implementation of the Chi-Toku-Tai principle, and the integration of national policy with a holistic, child-centered educational approach.